Reviews. Issue 1 (1st September 2019) - Londrigan, Michael P.; Blanco F., José
Menswear Revolution: The Transformation of Contemporary Men's Fashion, Jay McCauley Bowstead (2018) London: Bloomsbury Visual Arts, 210 pp., ISBN 978-1-47428-900-9, h/bk, £67.50Peacock Revolution: American Masculine Identity and Dress in the Sixties and Seventies, Daniel Delis Hill (2018) London: Bloomsbury Visual Arts, 210 pp., ISBN 978-1-3500-5643-5, h/bk, £85.00